Analisis Angka Lempeng Total Minyak Balur Kombinasi VCO dan Cabai Jawa (Piper retrofractum Vahl.) dengan Variasi Suhu Pemanasan - Sari, Luh De Cintya Kartika; Pramitha, Dewa Ayu Ika; Wardani, I Gusti Agung Ayu Kusuma (Usadha, 2022)
Balur oil combined with VCO and Javanese long pepper is a liquid herbal ingredient obtained from the fruit of the Javanese long pepper (Piper retrofractum Vahl.) with the addition of coconut oil (Cocos nucifera). This study was conducted to analyze the microbiological quality of VCO and Javanese long pepper combined balur oil to determine the safety of combined VCO and Javanese long pepper balur oil using the Total Plate Count (ALT) method. Balur oil combined with VCO and Javanese long pepper was made into 3 samples with different heating temperatures. Sample 1 is balur oil with a heating temperature of 40°C, sample 2 is balur oil with a heating temperature of 50°C, and sample 3 is balur oil with a heating temperature of 60°C. The results showed that the three samples of balur oil combined with VCO and Javanese long pepper with variations in heating temperature had different total microbial values, namely 3, 0, and 6 CFU/mL. Sample 1 had a total microbial value of 3 CFU/mL, sample 2 had a total microbial value of 0 CFU/mL, and sample 3 had a total microbial value of 6 CFU/mL. The three samples of VCO and Javanese long pepper combination oil had a total safe microbial value because they had not exceeded the maximum allowable microbial contamination limit according to BPOM No. 32 of 2019, namely 107 colonies/mL.